Characteristics of Balms (Balsams) as drugs and cosmetics. Analysis of domestic pharmaceutical market - Fedorovska, Mariana; Sliptsova, Natalia (Annals of Mechnikov's Institute, 2026)
The aim of the study. Data systematization of Ukrainian regulatory documents regarding the definition of Balms (Balsams) as medicinal and cosmetic remedies, their classification, formulation peculiarities and application; study of the domestic market of drugs and cosmetics distributed in the dosage form of Balms (Balsams). Materials and Methods. The data sources included the publications of domestic and foreign scientists, the State Register of Medicinal Products of Ukraine, the Compendium reference book, mobile application tabletki.ua. Information-analytical and marketing research methods were used. Results. "Balsams" as plants raw materials, are a type of oleoresins containing solutions of diterpenes in benzoic and/or cinnamic acids and their esters, namely: balsam of Peru, balsam of Tolu, benzoin, storax. They have a long history of applications in medicine, aromatherapy and cosmetology. An analysis of the nomenclature, composition of APIs and excipients, as well as the medical use of registered drugs in the dosage form "balm", and those drugs that use the term "balm" in their trade name was conducted. We have proposed terms to define “Balms for oral application” and “Balms for cutaneous application”. The definition, expanded classification, formulation ingredients of cosmetic balms for various functional purposes are provided. Conclusions. Today in Ukraine there are no valid regulatory documents regulating the definition and quality control of both medicinal and cosmetic Balms (Balsames). However, on the pharmaceutical and, especially, on the cosmetic market, drugs and cosmetic products called Balsames (Balms) are widely represented. All medical and cosmetic Balms regardless of their functions contain complex of active plant ingredients and cause intense action on the skin, their appendages or whole body.